THU0059 INCREASING SURFACE LUBRICATION WITH POLY(2-METHYL-2-OXAZOLINE) HALTS DEGENERATIVE CHANGES IN THE CARTILAGE IN A COLLAGENASE INDUCED OSTEOARTHRITIS (CIOA) RAT MODEL. (2nd June 2020) - Kauppinen, S.; Fercher, D.; Barreto, G.; Morgese, G.; Benetti, E.; Saarakkala, S.; Nieminen, H.; Zenobi-Wong, M.; Finnilä, M. A.
Abstract : Background: Degenerative lesions of articular cartilage (AC) surface are related to disruption of the well-organized collagen network and allow proteoglycans to escape from the tissue. Ultimately, this leads to the development of osteoarthritis (OA). Targeted therapy for early AC lesions could provide an effective way to halt the OA development process. Objectives: This study aims to evaluate the effectiveness of an engineered surface lubricant; poly(2-methyl-2-oxazoline) (PMOXA) 1 to prevent the destruction of the AC surface. Our recently developed contrast-enhanced µCT (CEµCT) method was used to quantify AC surface erosion 2 . Methods: OA was induced in 12-18 week-old male Wistar rats (N=17) with an injection of 250 U Collagenase within 25 µL solution into the left hind limb. Both hind legs were treated with a second injection three days after the collagenase injection (CI). Three groups were formed by using either PMOXA (N=5), hyaluronic acid (HA; N=6), or saline (N=6) during the second injection. The animals were sacrificed after 45 days, and harvested knees were fixed in phosphate-buffered formalin for a week. Knees were stored in 70% ethanol, and tibia and femur were carefully dissected free of other tissue, stained with 1% phosphotungstic acid 3, and scanned with a desktop µCT with 2.8µm pixel size. The medial and lateral AC surfaces were manually segmented from 3D projections using an in-house developed program (Matlab sofware). These surfaces were analyzed by iteratively fitting a reference surface (RS) to a median-filtered smoothed surface representing a perfectly smooth surface, capturing the realistic shape AC. An offset of 5 pixels (14 µm) was added between the RS and the original surface (OS). Two quantitative parameters were calculated from the data: Average of Maximum Void Depth (MVD) (depth of lesion) and Degeneration-% (area exceeding 20 µm MVD / whole area) *100). Estimates of mean differences from all groups against the CI+Saline -group were determined using a linear mixed model. Results: Boxplots from tested groups are shown in Fig. 1A and MVD results are visualized in Fig. 1B . Collagenase caused structural defects only on the medial and lateral tibial AC surfaces, which was seen as increased MVD and Degeneration-%. CI changes were not seen in PMOXA or HA treated groups. Furthermore, MVD and Degeneration% were lower in CI knees that were treated with PMOXA. Conclusion: Our CEµCT analysis method was able to detect subtle changes of the AC surface in the medial and lateral tibial cartilage, caused by the CI. In contrast, the CI did not cause detectable changes in the AC of the femur, which indicates that in the CIOA model, the tibia is more susceptible to structural degradation. Our results show that early intervention with HA or PMOXA can halt the degenerative AC changes caused by CI. However, HA did not suppress the effects of CI in the medial tibia, which indicates that PMOXA could be more effective to prevent the development of OA. References: [1]Morgese G, et al. Hairy and slippery polyoxazoline-based copolymers on model and cartilage surfaces. Biomacromolecules 2018 19 (2), 680-690 [2]Ylitalo T, et al. Quantifying Complex Micro-Topography of Degenerated Articular Cartilage Surface by Contrast-Enhanced Micro-Computed Tomography and Parametric Analyses. J Orthop Res. 2019 Apr;37(4):855-866. [3]Nieminen HJ, et al. Determining collagen distribution in articular cartilage using contrast-enhanced micro-computed tomography. Osteoarthritis Cartilage. 2015;23(9):1613–1621 Disclosure of Interests: None declared